Normal fault linkage and reactivation, Dampier Sub-basin, Western Australia - McHarg, S.; Elders, Chris; Cunneen, J. (Taylor & Francis Co Ltd, 2018)
The Northern Carnarvon Basin of Western Australia has experienced a polyphase deformation history during the breakup of Gondwana. Extension during the Carboniferous–Permian and a subsequent Early Jurassic rift event imposed two distinct fault systems, separated by a several kilometre-thick Triassic sedimentary sequence. Inboard areas, where Triassic sequences are thinner, Jurassic faults both detach above and also penetrate into Permian sequences. Other large-scale faults demonstrate a vertical hard/soft linkage between the two fault systems. In outboard areas where the Triassic is thicker, the relationship is less clear owing to the lower resolution of Permian sequences in seismic data. Here we undertake fault displacement analysis on three faults on the southern margin of the Exmouth Plateau to investigate the growth mechanism of Jurassic-aged faults and possible structural influence of deeper Permian faults. We find evidence of low-throw faults restricted to Mesozoic strata as more complex-segmented faults that have nucleated at a depth below that resolvable on seismic data. When considered in a regional context, the nature of faults in this study suggest oblique reactivation of the NE-trending Permian fabric, under east–west-oriented extension.